Implementasi K-Means Clustering Analysis untuk Mengelompokkan Kelurahan-Kelurahan Di DKI Jakarta Berdasarkan Jumlah Positif Covid-19. - Nurul Qomariasih (CV. Syntax Corporation Indonesia, 2021)
Covid 19 is a disease caused by the Corona Virus, attacking the respiratory system, and worsening the condition of a person with congenital disease. Until now, the government has still determined the case of the COVID-19 outbreak as an emergency and established health protocols for its citizens. DKI Jakarta is one of the areas with the highest cases of covid 19. Therefore, this study is grouping or clustering urban villages in DKI Jakarta province into groups of urban villages with very high, medium, or low cases using the K-Means Clustering method . This grouping aims to provide information to the government and as one of the considerations in dealing with COVID-19 cases as well as prioritizing the provision of medical facilities and infrastructure. The K-Means Clustering study with standardized data using Euclidean distance succeeded in grouping urban villages in DKI Jakarta into 3 groups.